Clinical trials for rapid changes in suicidal ideation: Lessons from ketamine. Issue 1 (24th February 2021) - Ballard, Elizabeth D.; Fields, Jessica; Farmer, Cristan A.; Zarate, Carlos A.
Abstract: Rapid‐acting treatments for suicidal thoughts are critically needed. Consequently, there is a burgeoning literature exploring psychotherapeutic, pharmacologic, or device‐based brief interventions for suicidal thoughts characterized by a rapid onset of action. Not only do these innovative treatments have potentially important clinical benefits to patient populations, they also highlight a number of methodological considerations for suicide research. First, while most clinical trials related to suicide risk focus on suicide attempts, new clinical trials that use suicidal thoughts as the primary outcome require a number of slight modifications to their clinical trial design. Second, the rapid onset of these new interventions permits an experimental therapeutics approach to suicide research, in which psychological and neurobiological markers are embedded into clinical trials to better understand the underlying pathophysiology of suicidal thoughts. The following review discusses these methodological innovations in light of recent research using the N‐methyl‐D‐aspartate (NMDA) receptor antagonist ketamine, which has been associated with rapid effects on suicidal thoughts. We hope that "lessons learned" from the ketamine literature will provide a blueprint for all researchers evaluating rapid‐acting treatments for suicidal thoughts, whether pharmacologic or psychotherapeutic.